A study of e-government system effectiveness: applying structuration theory to context-aware ICT applications in public organisations. (10th October 2008) - Tseng, Paul T.Y.
This paper is based on Giddens' structuration theory to discover what constitutes the effective use of Electronic Government Information System (EGIS) through empirical method. It investigates how to enable EGIS effectiveness among people, technology, and organisation within a public organisational context. Usable 152 respondents data are chosen from the Bureau of Foreign Trade (BOFT) and the Department of Commerce (DoC) within the Ministry of Economic Affairs, Taiwan. Causal analysis was conducted to explore the relationships among the research variables. The results indicate that the impact of ICT environment, institutional properties, and human factors on the effectiveness of EGIS is fully mediated by how the public employees use EGIS.